A revision of Ophidiaster davidsoni de Loriol and Pellat 1874 from the Tithonian of Boulogne (France) and its transfer from the Valvatacea to the new forcipulatacean genus Psammaster gen. nov. - M. Fau; L. Villier; T. A. M. Ewin; A. S. Gale; A. S. Gale (Fossil Record, 2020)
Forcipulatacea is one of the three major groups of extant sea stars (Asteroidea: Echinodermata), composed of 400 extant species, but only known from fewer than 25 fossil species. Despite unequivocal members being recognized in the early Jurassic, the evolutionary history of this group is still the subject of debate. Thus, the identification of any new fossil representatives is significant. We here reappraise Ophidiaster davidsoni de Loriol and Pellat 1874 from the Tithonian of Boulogne, France, which was assigned to another major extant group, the Valvatacea, and reassign it within a new forcipulatacean genus, Psammaster gen. nov. Psammaster davidsoni gen. nov. possess key Forcipulatacea synapomorphies including compressed ambulacrals and adambulacrals and typical organization of the body wall and arm ossicles. A phylogenetic analysis including Psammaster davidsoni gen. nov. does not place it within any existing forcipulatacean family. Instead, Psammaster davidsoni gen. nov. exhibits a mix of plesiomorphic and derived characters and is resolved as a sister clade to a large group including the Asteriidae, Stichasteridae, and Heliasteridae. Removal of this species from the Ophidiasteridae means their oldest fossil representative now dates from the Santonian, Upper Cretaceous.